Incidence of Endophthalmitis after Bevacizumab (Avastin) - Qasim Lateef, Syed Ali Haider, Hussain Ahmad Khaqan (Pakistan Journal of Ophthalmology, 2012)
Purpose: To assess the rate of infectious endophthalmitis after an intravitreal injection of Bevacizumab (Avastin). Material and Methods: The patients undergoing intravitreal injections of antivascular endothelial growth factor Bevacizumab (Avastin) from June 1st, 2006, through to June 30, 2011 were followed up for one month after injection at Unit 3, Department Of Ophthalmology, Lahore General Hospital, Lahore to determine rate of infectious endophthalmitis after an intravitreal injections of antivascular endothelial growth factor Bevacizumab (Avastin). Results: 7 (0.134%) cases of clinically suspected endophthalmitis were identified after a total of 5189 intravitreal injections of antivascular endothelial growth factor (Avastin). The mean interval between intravitreal anti VEGF injections and onset of symptoms was 2.55 days. The interval between onset of symptoms and examination was average 4 days. Conclusion: Endophthalmitis remains an infrequent but severe complication of intravitreal injections of Bevacizumab (Avastin). Using a strict injection protocol may help in reducing the incidence of infection.